PERANAN INFLUENCER DALAM MENINGKATKAN PENJUALAN PRODUK SELAMA KONDISI PANDEMI - Lingga Yuliana; Adrian A. Wijanarko; Andri Mat Raharjo; Sri Harnanih; Maya Firdiana (Politeknik Ubaya, 2022)
Pandemic conditions which occur all over the world are no exception in Indonesia, causing the Indonesian people's economic activity to halt for a time. This is an opportunity for enterprises to survive amid the present epidemic if they can run activities online. Entrepreneurs with local brands require help from influencers to drive sales of their present items, in addition to depending on social media and other e-commerce sites. The goal of this research is to look into the function of influencers in boosting product sales during a pandemic. The pandemic has slowed the economy and decreased people's willingness to spend. This research focuses on an influencer named Michie (@browspecialist), who worked with a number of local brands throughout the pandemic in 2020. The study employed a descriptive qualitative approach using a random sample procedure. The findings of the study show that influencers can boost sales of local brand products by partnering for a set amount of time. Because it can run out quickly, the partnership improves sales.